(untitled) - Anderson, Dave (Hoboken, N.J., 2005)
This is not your typical business book. You won't find academic remedies to your business challenges or exhortations to create a warmer and fuzzier workplace. In fact, you'll find the opposite-tips on how to be a tougher, take-no-prisoners-style manager. It's time to stop letting workplace political correctness push you around and get serious about your business.
Keywords: Leadership,Personnel management,Organizational effectiveness,Performance standards,Lãnh đạo,Quản lý nhân sự,Hiệu quả cơ quan